Landscape heterogeneity buffers the impact of an extreme weather event on wildlife - Laura R. Prugh; Jessica D. Lundquist; Benjamin K. Sullender; Calum X. Cunningham; Jack Dechow; Bridget L. Borg; Pamela J. Sousanes; Sarah Stehn; Michael T. Durand (Communications Biology, 2024)
Abstract Extreme weather events are becoming more frequent, with poorly known consequences for wildlife. In December 2021, an atmospheric river brought record-shattering amounts of rain and snow to interior Alaska, creating conditions expected to cause mass mortality in grazing ungulate populations that need to access ground forage. We characterized snowpack conditions following the storm and used a 36-year monitoring dataset to quantify impacts on caribou (Rangifer tarandus) and their primary predator, wolves (Canis lupus). December precipitation was 7.3 SD above the 99-year mean and 2.5-fold higher than the prior record, with a return period of 333 years. However, ice thickness within the snowpack was highly variable across vegetation types, and caribou shifted to use higher elevations that can blow free of snow. Caribou and wolf mortality rates were 1.3–1.8 SD above normal and caribou population growth rates were low but similar to recent years, indicating a surprisingly weak demographic response. These findings indicate that landscape diversity may bolster resistance of wildlife populations to short-term, potentially devastating effects of extreme weather.